Ejercicio de la competencia constitucional del Centro de Rehabilitación Social de Quevedo, por el Gobierno Autónomo Descentralizado Municipal del Cantón Quevedo. - Domínguez Espinel, Julio César (2017)
This project entitled legal research analyzes the relations hips established between the legal and social requirements in this respect, where punctuated problem areas in the legal standard of exercise of powers, determined the need for research and a proposal for the amendment to Chapter IV of COOTAD. To this end, the importance of efficient public institutions that provide quality services to the population and to meet their specific functions is discussed; however, many of them are not able to achieve their purposes, such as the Center for Rehabilitation of Quevedo,